Application of Intelligent Computation to Promote the Automation of Flight Control Design - Zhang, Ming-tao; An, Jin-wen (ICICTA : 2008 International Conference on Intelligent Computation Technology and Automation : 20-22 October 2008, 2008)
As the systems to be controlled are becoming more and more complex, more difficulties arise when trying to get excellent performance. In the grand trend of multi-subjects amalgamation, intelligent computation is widely applied to optimize controller parameters. Intelligent computation being inspired from biology evolution, which has formed their own ingenious structures through a long period, is suitable to settle complex problems and to realize intelligent control. Intelligent computation is applied to conventional control designs to improve them. At present practical flight control design makes use of conventional methods, which are characterized as linearization of nonlinear problems. In the conventional flight control design, there is heavy work of controller parameter tuning. Intelligent computation is applied to optimize the controller parameters and farther on to realize the automation of controller parameter tuning. It can save designers a lot of energy and better results can be obtained.